2020
DOI: 10.14202/vetworld.2020.1091-1097
|View full text |Cite
|
Sign up to set email alerts
|

The influence of "Stimix Zoostim" and "Normosil" probiotics on fecal microflora, hematologic indicators, nutrient digestibility, and growth of mother-bonded calves

Abstract: Aim: This paper presents the results of the studies on "Stimix Zoostim" and "Normosil" probiotics and their influence on fecal microflora, hematologic indicators, immunoresistance, nutrient digestibility, and growth intensity of mother-bonded calves. Materials and Methods: The calves of the control group were fed with their basic diet (BD) without "Stimix Zoostim" or "Normosil", whereas the calves of the experimental group were fed with their BD supplemented with "Stimix Zoostim" and "Normosil". For 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Some studies have shown that probiotics can promote total dry matter intake (TDMI), body weight (BW), and growth rate of calves [ 5 , 6 ]; others have concluded that probiotics do not affect the growth performance or feed efficiency [ 7 , 8 ]. Additionally, some studies have found that probiotics can increase blood IgA, IgG, and IgM concentrations and correspondingly improve the immunity of calves [ 9 ]; others observed no effect of probiotics on the concentration of these three immune globulins [ 10 ]. Furthermore, some studies have identified that probiotics can reduce faecal scores of calves [ 11 , 12 ]; other reported no differences on faecal scores by adding probiotics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that probiotics can promote total dry matter intake (TDMI), body weight (BW), and growth rate of calves [ 5 , 6 ]; others have concluded that probiotics do not affect the growth performance or feed efficiency [ 7 , 8 ]. Additionally, some studies have found that probiotics can increase blood IgA, IgG, and IgM concentrations and correspondingly improve the immunity of calves [ 9 ]; others observed no effect of probiotics on the concentration of these three immune globulins [ 10 ]. Furthermore, some studies have identified that probiotics can reduce faecal scores of calves [ 11 , 12 ]; other reported no differences on faecal scores by adding probiotics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are considered beneficial for the gastrointestinal tract as an alternative to antibiotics (Khaziakhmetov et al, 2020). Intestinal microflora plays a vital role in the assimilation of organic substances.…”
Section: Introductionmentioning
confidence: 99%